Iodothiocyanation/Nitration of Allenes with Potassium Thiocyanate/Silver Nitrite and Iodine. Issue 19 (25th August 2016) - Yang, Xiaodong; She, Yue; Chong, Ya; Zhai, Huichun; Zhu, He; Chen, Baohua; Huang, Guosheng; Yan, Rulong
Abstract: Direct strategies for the iodothiocyanation and iodonitration of allenes have been developed. In this process, potassium thiocyanate/silver nitrite and molecular iodine are used as the source of SCN, ONO2 and iodine to provide the desired products in moderate to good yields with high stereoselectivity. Abstract :